Breaking boundaries in ankylosing spondylitis: how innovative cell therapies reshape immunity, drive cutting-edge advances, and face future challenges - Ke, Minxia; Liu, Wenli; Lu, Huimin; Pan, Xiafei; Wu, Mengyang; Qi, Nianmin; Wang, Zhiqiang; Wu, Yuehong; Zhang, Feng (Frontiers in Immunology, 2025)
Ankylosing spondylitis (AS) is a chronic autoimmune inflammatory disease primarily affecting the axial skeleton, characterized by joint erosion and ankylosis. AS significantly impacts quality of life, work capacity and mental health through chronic pain, stiffness and functional decline. Its pathogenesis is multifactorial, involving genetic predispositions, immunological dysregulation and environmental triggers. Current treatments, including nonsteroidal anti-inflammatory drugs and immunosuppressive agents, offer limited symptomatic relief and fail to improve long-term prognosis due to efficacy limitations and side effects. Recent advances in cell therapy, particularly mesenchymal stem cells (MSCs) and chimeric antigen receptor (CAR) T-cell therapy, demonstrate promise in addressing these limitations by providing immunomodulatory, anti-inflammatory and regenerative benefits. This review summarizes the pathogenesis of AS, the limitations of existing treatments and the clinical progress of MSC therapy, while exploring the potential of emerging CAR-based therapies.